Industrial Flow Measurement - Spitzer, David W. (ISA, 2004)
Annotation Designed to help practicing engineers avoid costs associated with misapplication of flowmeters, this newly revised text reviews the important concepts of flow measurement and provides explanations, practical considerations, illustrations, and examples of current flowmeter technology. Modern flowmeters handle many more applications that could have been imagined a few centuries ago. Today's flow measurements encompass operating conditions that range from capillary blood flow, to flows over spillways, to flow of gases, plasmas, pseudo-plastics, solids, and corrosives, to name but a few. This book presents a rational procedure for flowmeter selection that is based on factual information and will help the professional evaluate the appropriate criteria to arrive at proper flowmeter selection.
Keywords: elektronické knihy; electronic books